Stewards in an "Odd" Kingdom: Performance and Remuneration of the Boards of Directors of NHS Foundation Trusts. Issue 6 (5th December 2020) - García-Lacalle, Javier; Royo, Sonia; Yetano, Ana
ABSTRACT: Performance measures and rewards are becoming commonplace in public sector organizations. This article studies the implementation of performance-related pay (PRP) mechanisms in the boards of directors of the Foundation Trusts (FTs) of the National Health Service (NHS) in England and analyzes whether their remuneration is linked to organizational performance using qualitative and quantitative analyses (structural equation model). FTs operate in a favorable context for implementing PRP to remunerate executive directors. Our results show that many FTs have not implemented PRP and hardly any report having payed bonuses. However, most of them disclose that they carry out some kind of performance appraisal. These results indicate both reluctance to and difficulties in adopting PRP in public sector entities. Results also suggest that executive directors of NHS FTs are stewards in an "odd" kingdom that uses performance ratings to evaluate organizations, blaming directors when ratings are bad, but with no rewards when good performance is achieved.